Vesicouterine fistula – a rare delayed complication of cesarean section - Akter, Sumaya; Begum, Kohinoor; Saha, Joysree (Journal of Bangladesh College of Physicians and Surgeons, 2020)
A vesicouterine fistula is an abnormal pathway between the urinary bladder and the uterus. It is a rare urogynaecological fistula. In vesicouterine fistula, clinical presentations are cyclic haematuria (menouria), amenorrhoea, urinary continence which mimics Youssef’s syndrome. This case presents, a 37 year old multiparous woman with vesicouterine fistula which she developed 8 years after cesarean section. Diagnosis was confirmed by cystoscopy and fistula was repaired through trans abdominal surgery. She regained normal vaginal menses 4 months after surgery. J Bangladesh Coll Phys Surg 2020; 38(4): 209-212